2009
DOI: 10.1183/09031936.00109309
|View full text |Cite
|
Sign up to set email alerts
|

Does cannabis use predispose to chronic airflow obstruction?

Abstract: C annabis (derived from the ubiquitous plant, Cannabis sativa, and also known as marijuana) is the most widely used illicit drug worldwide, as well as the second most commonly smoked substance after tobacco, with an estimated 166 million users (3.9% of 15-64 yr olds) [1]. Its wide popularity is due to the euphoric effects of its major psychoactive ingredient, D 9-tetrahydrocannabinol (THC). Since the gas and particulate phase constituents of the smoke of marijuana are at least qualitatively similar to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Lower FEV1/FVC in marijuana smokers, however, can be explained at least partly by a tendency towards higher FVC or total lung capacity 28,29,32 . A recent longitudinal study, which demonstrated significantly higher FVC and total lung capacity with marijuana exposure, strongly supports this notion 13,20 , as does our study.…”
Section: Commentsupporting
confidence: 92%
See 3 more Smart Citations
“…Lower FEV1/FVC in marijuana smokers, however, can be explained at least partly by a tendency towards higher FVC or total lung capacity 28,29,32 . A recent longitudinal study, which demonstrated significantly higher FVC and total lung capacity with marijuana exposure, strongly supports this notion 13,20 , as does our study.…”
Section: Commentsupporting
confidence: 92%
“…Prior studies of marijuana and pulmonary function have yielded apparently conflicting results 1013 . Many studies have focused on the ratio of FEV1/FVC, lower values of which suggest the presence of airway obstruction, and have found either no association 10,20,27 or lower FEV1/FVC with marijuana use 2832 .…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, previous studies have not always found strong or consistent evidence that cannabis smoking has adverse effects on objective measures of COPD such as the FEV1/FVC ratio. 24,25 The present study did find evidence of such effects, over and above those that appeared attributable to the tobacco use of cannabis smokers. It has been suggested that discrepancies in the evidence partly relate to the extent that cannabis use is associated with increased FVC (which may result from repeated pulmonary hyperinflation related to the way cannabis is smoked.…”
Section: Comparison With Existing Literaturementioning
confidence: 44%